2020
DOI: 10.3390/w12041149
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Water Distribution Network with Key Performance Indicators for Spatio-Temporal Analysis and Operation of Highly Stressed Water Infrastructure

Abstract: An annual and lumped water balance assessment of a water distribution network is recommended by the International Water Association as a first step and prerequisite for improving the performance of the network by minimizing real/physical water losses, burst incidents, water theft, nonrevenue water, and energy consumption, among others. The current work suggests a modeling approach for developing the water balance of a network spatio-temporarily, in hour time-scale and neighborhood granularity. It exploits alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Specifically, the residual service lives of decommissioned water tanks should be assessed [22] to better manage water supply systems. As drinking water supply systems are vulnerable both spatially and temporally, it is important to use key performance indicators (such as leakage reduction, pressure-driven demand reduction and energy and economic savings) [23] for the improvement of water distribution system management. High operating pressure is responsible for high leakage rates, while low operating pressure increases water age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the residual service lives of decommissioned water tanks should be assessed [22] to better manage water supply systems. As drinking water supply systems are vulnerable both spatially and temporally, it is important to use key performance indicators (such as leakage reduction, pressure-driven demand reduction and energy and economic savings) [23] for the improvement of water distribution system management. High operating pressure is responsible for high leakage rates, while low operating pressure increases water age.…”
Section: Discussionmentioning
confidence: 99%
“…Key performance indicators to be used for the improvement of water distribution system management with detailed spatio-temporal supervision are introduced in [23]. The results showed that losses depict intense seasonal variability, while spatial variability, which is linked to the elevation and the different urban land uses, is proven to play a significant role in the neighborhoods' water balances.…”
Section: Drinking Water Supply Systemsmentioning
confidence: 99%
“…The model attempts to show the possible evolution of water demand, so the demand-driven pressures were included in the simulation, i.e., billed authorized consumption (as metered from WUS) and apparent losses (theft and metering inaccuracies). The components of the IWA water balance table specifically for the case of Skiathos were recently described by Kofinas et al (2020), so the respective seasonal estimations were used in the model per quarter (as percentage increment of consumption): 5.57% for January-March, 8.8% for April-June, 17.05% for July-September and 23.61% for October-December. The real losses are also very high, but since there were no available data on the physical water availability, in order to simulate the hydrological water balance (i.e., the actual supply pressures), the analysis discusses the demand (human-driven) side.…”
Section: Methodsmentioning
confidence: 99%
“…The main settlement is the city of Skiathos (4,992 habitants), served by a pipeline network, suffering from losses and leakages (around 60% in total). The annual real losses are approximately 51%, the annual apparent losses 6%, and the annual water theft is at least 3.6% of the system input volume, according to Kofinas et al (2020).…”
Section: Study Areamentioning
confidence: 99%
“…The permanent residents are about 6000, while the island population grows rapidly during the tourist season lasting from April to early October [21]. The water demand presents high seasonal variability peaking in August when water pumping shows an increase often exceeding 130% of the winter minimum, indicating a link between touristic activity and the water demand [22]. The entire island water network is served by one drilled well, supported by a smaller well when required, which results in serious water supply issues for the island.…”
Section: Case Studymentioning
confidence: 99%